Unusual case of retrosternal chest pain: a twist in the tale - Ike, Irene Mary (BMJ Case Rep, 2021)
A 62-year-old man was referred to the emergency department with retrosternal chest pain for 4 days. Coronary angiogram and ECG showed no occlusion of coronary vessels. Contrast-enhanced CT of thorax showed b/l pleural effusion, pneumomediastinum, right hydropneumothorax, with the underlying collapse of lungs and intercostal drainage tube in situ. Intercostal tube showed purulent discharge. Repeat oral contrast did not show any leakage through the upper gastrointestinal tract, and the patient is admitted to the intensive care unit following endotracheal intubation. However, an upper gastrointestinal endoscopy, performed at the bedside in the intensive care unit unexpectedly revealed a foreign body (piece of coconut shell) impacted at the lower oesophagus. The foreign body was removed successfully using oesophagoscopy, and the patient made a full recovery following multidisciplinary teamwork between critical care and surgeons.